PENGARUH INOVASI PRODUK, MEREK DAN MOTIVASI TERHADAP KEBERLANGSUNGAN USAHA CAFE COFFEE DI KOTA MEDAN - IKA PUSPA SATRIANNY; NICO FERNANDO (JURNAL ILMIAH KOHESI, 2021)
Cafe Coffe's business is the same as the café business which generally serves food and beverages that are relatively the same type of food and beverages and do not have innovations regarding the food and beverage products served, so that product variations cannot be done, thus affecting the brand image of Cafe Coffe, where the Cafe Coffe brand is not yet clearly known by consumers, so that the existing visitors are just that-that's all. This makes the business motivation of the owner of Cafe Coffe has not yet appeared to fix this and also to create the food and beverage products that are served, so that the business that was initiated only revolves around the same consumers and runs in place. This study aims to find out how the influence of Cafe Coffe product innovation, cafe coffe brand and the business motivation of Cafe Coffe owners have a significant effect on the sustainability of Cafe Coffe's business. TThe results of the study can be concluded that simultaneously the variables of product innovation at Cafe Coffe, the Cafe Coffee brand and the business motivation of the owner of Cafe Coffee have a significant effect on the sustainability of the Cafe Coffe business, while partially only the variables of innovation of Cafe Coffee products and the Cafe Coffe brand have a significant effect on the variables of cafe coffee business continuity.